SEVERITY LEVEL IN HYPOSPADIAS PATIENTS AT HASAN SADIKIN HOSPITAL BANDUNG 2019-2023 - Jaidi, Wa'el; Sibarani, Jupiter (Indonesian Journal of Urology, 2025)
Objective: The aim of this study is to determine the level of severity in hypospadias patients at Hasan Sadikin Hospital Bandung from 2019—2023. Material & Methods: This is a descriptive and observational study. The data collected includes information from all patients with hypospadias who underwent treatment at the hospital from January 2019 to November 2023, meeting the inclusion criteria and selected through total sampling. The data were presented using descriptive statistics in frequency and percentage. Results: The incidence of hypospadias at Hasan Sadikin Hospital in Bandung from 2019 to 2023 was 296 patients, with an average age of 8.6 ± 6.9 years, and the age group of 0–5 years being the most affected. Out of the total, 163 patients (56%) had moderate hypospadias, 99 patients (33%) had severe hypospadias, and only 34 patients (11%) had mild hypospadias. The average scores were G (glans) 2.2 ± 0.9, M (meatus) 3.4 ± 0.9, and S (shaft) 3.1 ± 1.0. Conclusion: In conclusion, early detection and surgical intervention faced no obstacles, and public awareness of this condition is good. Key words: Hypospadias, severity level, Hasan Sadikin.